Core Inflation - Why the Federal Reserve Got it Wrong - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2008)
This paper introduces a new estimate of core inflation. Core inflation is a real time estimate of monetary inflation. Most existing core inflation estimate do not account for persistent relative price changes and are therefore likely to be poor estimates of the underlying monetary inflation rate. The proposed core inflation estimate estimates core inflation by first estimating the inflation signal in all price series from the price index with a wavelet based signal estimation algorithm. In the second step the weighted inflation average is calculated by using the expenditure weights from the price index as weights. Relative price changes are thus accounted for under the assumption that the household must apply to its long run budget restriction. The proposed estimate of core inflation is estimated using data from the United States and the United Kingdom. It is evaluated by comparing it to existing estimates of core inflation. The empirical analysis show that the proposed estimate has a smaller forecasting error of future inflation than the other estimates and that it rapidly responds to increases in monetary inflation.
Keywords: E31; E52; 330; Core Inflation; Signal Estimation; Wavelets